2017
DOI: 10.1097/ta.0000000000001347
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative endovascular balloon occlusion of the aorta in trauma patients in youth

Abstract: Epidemiologic study, level III; therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Children are more radiosensitive and have a higher risk of carcinogenesis 22 , therefore clinicians are hesitant to perform pan-scan CT in young children. Treatment procedures frequencies such as operations and interventional radiology are low, which may be due to technical difficulties 23 , and thus conservative management is generally accepted in pediatric trauma patients 24,25 . On the other hand, the trend of diagnostic choice between early and late phase demonstrated that the use of pan-scan CT increased regardless of the reduction of severe pediatric injury (Supplemental Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Children are more radiosensitive and have a higher risk of carcinogenesis 22 , therefore clinicians are hesitant to perform pan-scan CT in young children. Treatment procedures frequencies such as operations and interventional radiology are low, which may be due to technical difficulties 23 , and thus conservative management is generally accepted in pediatric trauma patients 24,25 . On the other hand, the trend of diagnostic choice between early and late phase demonstrated that the use of pan-scan CT increased regardless of the reduction of severe pediatric injury (Supplemental Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…A 12 year review from the Japanese National Database, identified 19,467 pediatric patients under 18 years of age, 54 of which had a REBOA deployed with 15 of those patients under the age of 16. This younger patient cohort demonstrated an overall survival rate of 53.3% compared to 38.5% of the adolescents aged 16–18 years old (3). Other clinical end points such as occlusion time, height, weight, coagulation were not analyzed nor were complications such as embolism, acute kidney injury (AKI), or other ischemic events (3).…”
Section: Introductionmentioning
confidence: 88%
“…This younger patient cohort demonstrated an overall survival rate of 53.3% compared to 38.5% of the adolescents aged 16–18 years old (3). Other clinical end points such as occlusion time, height, weight, coagulation were not analyzed nor were complications such as embolism, acute kidney injury (AKI), or other ischemic events (3). Due to the lack of clinical evidence, the Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) device is not yet FDA approved for pediatric patients.…”
Section: Introductionmentioning
confidence: 88%
“…The use of REBOA in the pediatric population is even more controversial since only isolated reports are available. Apart from a couple of case reports, there is only one study that has evaluated the efficacy of REBOA in pediatric trauma patients [7,15,16]. Previous requirements for using large sheaths (12 Fr) has probably been the reason that REBOA has not been considered in young patients.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence in the pediatric population is even more limited with only one retrospective observational cohort publication from the Japanese Trauma Data Bank. This includes 54 severely injured children and suggests REBOA as a reasonable option in the pediatric population [7].…”
Section: Introductionmentioning
confidence: 99%